The ecology and mortality of swans at the Ouse Washes, England - Owen, Myrfyn; Cadbury, C J (Wildfowl, 1975)
The ecology and feeding behaviour of Mute Cygnus olor, Whooper C. cygnus cygnus and Bewick's Swans C. columbianus bewickii over six winters 1969-1975 at the Ouse Washes, England, is described. An analysis is made of the winter mortality of swans at the site. The swans exploited three distinct food sources during the period: natural vegetation on the washes, grain which was specially provided and crops, particularly waste potatoes, on adjoining farmland. When feeding on the meadows, swans preferred soft grasses, Agrostis stolonifera, Alopecurus geniculatus and Glyceria fluitans, to the coarser species also available. Glyceria maxima was, however, an important late winter food. The starchy roots of Rorippa palustre were a prominent constituent in the diet in the first two winters after which the plant decreased. Seeds of wetland plants and animal material made an insignificant contribution to the diet. Once supplementary feeding with grain started a large proportion of the swans made use of it. Since the 1972-1973 winter many Bewick's Swans have fed on waste crops, particularly potatoes, on neighbouring fenland farms. It is suggested that the change was brought about by increase in swan usage following the creation of a large undisturbed refuge, and possibly by the birds searching for high-energy foods to replace declining Rorippa. Undisturbed swans on water increased their feeding activity during the day and continued to feed after dark. By contrast, when on farmland swans fed intensively in the morning and later afternoon with a period of relatively low activity at midday. On average about 3% of the Mute and Whooper Swan population and 1.4% of the Bewick's Swans at the Ouse Washes died each winter. Collisions with power lines (30%), poisoning from ingested lead pellets and fishing weights (29%) and shooting (8%) accounted for most of the deaths of 128 swans recorded over six winters. Birds are likely to ingest lead pellets as grit in this grit deficient area and the provision of grit in feeding areas or roost might lessen deaths from poisoning. Although the changes in diet are probably beneficial to the birds' nutrition, grain-feeding increases susceptibility to death from lead poisoning and flighting to and from the fenland farms increases mortality from collisions with power lines.